A national survey of state laws regarding medications for opioid use disorder in problem-solving courts - Barbara Andraka-Christou; Olivia Randall-Kosich; Matthew Golan; Rachel Totaram; Brendan Saloner; Adam J. Gordon; Bradley D. Stein (BMC, 2022)
Abstract Background Problem-solving courts have the potential to help reduce harms associated with the opioid crisis. However, problem-solving courts vary in their policies toward medications for opioid use disorder (MOUD), with some courts discouraging or even prohibiting MOUD use. State laws may influence court policies regarding MOUD; thus, we aimed to identify and describe state laws related to MOUD in problem-solving courts across the US from 2005 to 2019. Methods We searched Westlaw legal software for regulations and statutes (collectively referred to as "state laws") in all US states and D.C. from 2005 to 2019 and included laws related to both MOUD and problem-solving courts in our analytic sample. We conducted a modified iterative categorization process to identify and analyze categories of laws related to MOUD access in problem-solving courts. Results Since 2005, nine states had laws regarding MOUD in problem-solving courts. We identified two overarching categories of state laws: 1) laws that prohibit MOUD bans, and 2) laws potentially facilitating access to MOUD. Seven states had laws that prohibit MOUD bans, such as laws prohibiting exclusion of participants from programs due to MOUD use or limiting the type of MOUD, dose or treatment duration. Four states had laws that could facilitate access to MOUD, such as requiring courts to make MOUD available to participants. Discussion Relatively few states have laws facilitating MOUD access and/or preventing MOUD bans in problem-solving courts. To help facilitate MOUD access for court participants across the US, model state legislation should be created. Additionally, future research should explore potential effects of state laws on MOUD access and health outcomes for court participants.